MORAL TOKOH UTAMA DALAM NOVEL ALIF KARYA TAUFIQURRAHMAN AL-AZIZY - Wira Widyas Tuty; Edi Suyanto; Eka Sofia Agustina (Jurnal Kata (Bahasa, Sastra, dan Pembelajarannya), 2013)
The problem of this research is how are the moral aspects of the main character in the novel Alif written by Taufiqurrahman Al-Azizy. The aim of this research is to describe the moral aspects of  the main character in the novel Alif  written by Taufiqurrahman Al-Azizy and the worthiness  as a material lesson of literature in  SMA. The research method used is qualitative descriptive method. The data resource used is from the novel Alif written by Taufiqurrahman Al-Azizy. Collecting technique and data analysis used is text analysis. Based on the data analysis result found , the moral aspects of the main character  in novel Alif  written by Taufiqurrahman Al-Azizy include honesty, authentic values, the willingness to take responsibility, undependability, courage, modesty , realistic  and criticality. Novel Alif written by Taufiqurrahman Al-Azizy is worthy to be used as a material lesson alternative for students in SMA.Masalah penelitian ini adalah bagaimanakah aspek moral tokoh utama dalam novel Alif  karya Taufiqurrahman Al-Azizy. Tujuan penelitian ini untuk mendeskripsikan aspek moral tokoh utama dalam novel Alif  karya Taufiqurrahman Al-Azizy dan kelayakannya sebagai bahan ajar  sastra di SMA. Metode penelitian yang digunakan adalah metode deskriptif kualitatif. Sumber data dalam penelitian ini adalah novel Alif  karya Taufiqurrahman Al-Azizy. Teknik pengumpulan dan analisis data yang digunakan adalah analisis teks. Berdasarkan hasil analisis data ditemukan aspek moral tokoh utama dalam novel Alif  karya Taufiqurrahman Al-Azizy meliputi kejujuran, nilai-nilai otentik, kesediaan untuk bertanggung jawab, kemandirian moral, keberanian moral, kerendahan hati, realistik dan kritis. Novel Alif karya Taufiqurrahman Al-Azizy layak dijadikan sebagai alternatif bahan ajar siswa di SMA.Kata kunci: kelayakan, moral, tokoh utama.